Locomotor-respiratory coupling in wheelchair racing athletes: A pilot study - Perret, C.; Wenger, M.; Leicht, C. A.; Goosey-Tolfrey, V. L. (Frontiers in Physiology, 2016)
Purpose: In wheelchair racing, respiratory muscles of the rib cage are concomitantly involved in non-ventilatory functions during wheelchair propulsion. However, the relationship between locomotor-respiratory coupling (LRC: the ratio between push and breathing frequency), respiratory parameters and work efficiency is unknown. Therefore, the aim of the present study was to investigate the LRC in wheelchair racers over different race distances.